Total Knee Arthroplasty After Anterior Cruciate Ligament Reconstruction: Not Just a Routine Primary Arthroplasty. (1st February 2017) - Watters, Tyler Steven; Zhen, Yuan; Martin, J. Ryan; Levy, Daniel L.; Jennings, Jason M.; Dennis, Douglas A.
Abstract : Background: Despite the success of restoring joint stability and improving early functional outcomes after anterior cruciate ligament (ACL) reconstruction, the long-term risk of developing symptomatic osteoarthritis requiring total knee arthroplasty is higher than that in the uninjured population. The purpose of this study was to compare operative characteristics and early outcomes of patients undergoing total knee arthroplasty after ACL reconstruction with those of a matched cohort of control subjects with primary osteoarthritis and no history of ligament reconstruction. Methods: All patients who had undergone total knee arthroplasty from 2005 to 2013 at our institution with a history of ACL reconstruction and a minimum 2-year follow-up were identified from a prospective research database. These patients were matched by demographic and surgeon variables to patients who had not undergone prior ACL reconstruction. Outcomes included Knee Society Scores (KSS), range of motion, operative variables, complications, and reoperations. Results: A cohort of 122 patients was identified as the ACL study group and was compared with the matched control cohort. The mean age at the time of the surgical procedure was 58 years, and 55% of the patients were male. The mean follow-up was 3.3 years in the ACL group and 3.0 years in the control group. There was no significant difference in the latest KSS outcomes between groups postoperatively (p > 0.05). Although preoperative flexion was significantly lower (p = 0.01) in the ACL group (119°) than in the control group (123°), there was no difference between groups postoperatively. Fifty percent (61 of 122) of patients in the ACL group required implant removal at the time of total knee arthroplasty. The operative time was significantly longer (p < 0.001) in the ACL group (88 minutes) compared with the control group (73 minutes). There were a total of 11 reoperations in the ACL group, including 4 for periprosthetic infection, whereas there were only 2 reoperations in the control group. The risk of reoperation in the ACL group was more than 5 times higher than in the control group (relative risk, 5.5 [95% confidence interval, 1.2 to 24.3]; p = 0.01). Conclusions: The results of this retrospective matched cohort study suggest that prior ACL reconstruction results in longer operative time and increased risk of early reoperation after total knee arthroplasty. Level of Evidence: TherapeuticLevel III . See Instructions for Authors for a complete description of levels of evidence.